Occupational trichloroethylene exposure and non-Hodgkin's lymphoma: a meta-analysis and review. Issue 9 (27th April 2006) - Mandel, J H; Kelsh, M A; Mink, P J; Alexander, D D; Kalmes, R M; Weingart, M; Yost, L; Goodman, M
Abstract : Methods: Meta-analysis and review of 14 occupational cohort and four case-control studies of workers exposed to trichloroethylene (TCE) to investigate the relation between TCE exposure and the risk of non-Hodgkin's lymphoma (NHL). Studies were selected and categorised based on a priori criteria, and results from random effects meta-analyses are presented. Results: The summary relative risk estimates (SRRE) for the group of cohort studies that had more detailed information on TCE exposure was 1.29 (95% CI 1.00 to 1.66) for the total cohort and 1.59 (95% CI 1.21 to 2.08) for the seven studies that identified a specific TCE exposed sub-cohort. SRREs for three studies with cumulative exposure information were 1.8 (95% CI 0.62 to 5.26) for the lowest exposure category and 1.41 (95% CI 0.61 to 3.23) for the highest category. Comparison of SRREs by levels of TCE exposure did not indicate exposure-response trends. The remaining cohort studies that identified TCE exposure but lacked detailed exposure information had an SRRE of 0.843 (95% CI 0.72 to 0.98). Case-control studies had an SRRE of 1.39 (95% CI 0.62 to 3.10). Statistically significant findings for the Group 1 studies were driven by the results from the subgroup of multiple industry cohort studies (conducted in Europe) (SRRE = 1.86; 95% CI 1.27 to 2.71). The SRRE for single industry cohort studies was not significantly elevated (SRRE = 1.25; 95% CI 0.87 to 1.79). Conclusions: Interpretation of overall findings is hampered by variability in results across the Group 1 studies, limited exposure assessments, lack of evidence of exposure response trends, lack of supportive information from toxicological and mechanistic data, and absence of consistent findings in epidemiologic studies of exposure and NHL. Although a modest positive association was found in the TCE sub-cohort analysis, a finding attributable to studies that included workers from multiple industries, there is insufficient evidence to suggest a causal link between TCE exposure and NHL.